PENDEKATAN METODE SIX SIGMA-TAGUCHI DALAM MENINGKATKAN KUALITAS PRODUK (Studi Kasus PT. Asaputex Jaya Spinning Mill Tegal) - Nesvi Intan Oktajayanti; Mustafid Mustafid; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
The main factors to achieve business success in the era of globalization is the quality. In the business world, quality control is the key to maintaining customer loyalty. For a company doing quality control is expected to achieve the company's goals, related to the company's revenue. This is the purpose of PT. Asaputex Jaya Spinning Mill Tegal to make efforts to improve the production activities, especially in improving quality by reducing defects. Six Sigma-Taguchi method can be used to improve quality yarns product. From the analysis we found that the control diagram p, data of defects is uncontrolled, so the capability process is still low with capability value is 0,502. So, it need to be improved to enhance product quality yarns. By using the Taguchi method we can know factors and optimal level to improve the quality of the yarn. That Factor and level is TPI with the optimum level that can be used are Level 2 (13,5 rpm), level 1 (383 tpm) for Delivery Speed factor, for the weight of cotton the optimum level is level 1 (2,0 Kw) and factor Grain the optimal level is level 2 (400 Ne). Keywords: Six Sigma Method, Design Experiment of Taguchi, Capability Process